Utilization of a 3D Printed Orthodontic Distalizer for Tooth-Borne Hybrid Treatment in Class II Unilateral Malocclusions - Thurzo, Andrej; Urbanová, Wanda; Novák, Bohuslav; Waczulíková, Iveta; Varga, Ivan (Materials (Basel, Switzerland), 2022)
This paper introduces a novel method of 3D designing and 3D printing of a hybrid orthodontic tooth-borne personalized distalizer for treatment of unilateral Class II malocclusion. Research objectives were to clinically utilize 3D printed distalizers, appraise feasibility of this technique and compare two different biocompatible photopolymers (white and transparent). Frequency of distalizers' debonding and patients' aesthetical perception was evaluated on the set of 12 complete orthodontic treatments. The mean duration of treatment period with a bonded distalizer was 6.4 months. All cases were adults with unilateral Class II malocclusion managed with a hybrid approach as a part of Invisalign® comprehensive treatment. Results showed that such perspective practice is feasible for 3D design and in-office 3D printing of a personalized distalizer. Results also showed no clinically significant differences between both studied biopolymers. The paper discusses an evaluation of such personalized distalizer functionality with regard to the current state of the art and compares to conventional prefabricated alternatives like a Carriere® Distalizer™ appliance. Research showed a preference of patients towards transparent biocompatible photopolymer instead of the white A2 shade. The paper concludes that additive manufacturing from dental resins is a viable method in personalization and in-office 3D printing of orthodontic auxiliaries, particularly distalizers. New materials for orthodontic 3D printing endow enhanced individualization, thus more efficient treatment.
Keywords: computer modelling; unilateral class II; distalizer; dental photopolymers; personalized treatment; orthodontics; device customization; CAD/CAM; biocompatible 3D printing